Períodos de interferência e alternativas para o controle de plantas daninhas na cultura do melão - Carvalho, Donato Ribeiro (2020)
The cultivation of melon in the Brazilian semiarid region was carried out using practices that help to control weeds, such as the use of mulching, localized irrigation and the use of seedlings. However, these practices are not adequate to avoid the interference of damaged plants and the seedling transplant hole, being necessary to adopt measures to control the weed community. In this research, weed interference rates were applied in the hybrid of melon "Amarelo" and "Pele de Sapo", also assessing the selectivity and effectiveness of herbicides applied in the preemergence. The control period was determined during the years 2016 and 2017, with the procedures being arranged in a split plot scheme, with the parcels constituted by the melon hybrid (Amarelo and Pele de Sapo) and as subplots of the loss of living time or weed control. In order to evaluate the selectivity and effectiveness of herbicides, an experiment was carried out in a randomized block design, with four replications. The procedures were applied as herbicide applications Flumioxazin (35 g i.a. ha-1 ), Flumioxazin (25 g i.a. ha-1 ), Sulfentrazone (250 g i.a. ha-1 ), Metribuzin (480 g i.a. ha-1 ), Oxifluorfen ( 240 g i.a. ha-1 ), Oxifluorfen + Smetolachlor (240 g i.a. ha-1 + 960 g i.a. ha-1 ), Clomazone (360 g i.a. ha-1 ) and Clomazone + Oxyfluorfen (360 g i.a. ha-1 + 240 g i.a. ha-1 ), in pre-emergence of weeds. The presence of weeds reduced the increase in melon hybrids by 52%. The cultivation of melon favors the establishment of climbing species, such as Merremia aegyptia. Weed control should be started between the first and second weeks and the duration will be approximately 42 days, considering a loss of 5%. The herbicides metribuzin, ametryn and diuron cause the death of the melon crop. The applications of clomazone and the combination clomazone + oxyfluorfen were the most efficient in controlling weeds present in the study area, with low phytotoxic effects and less variation in melon yield